PLASMA PROFILE OF PROGESTERONE, ESTRADIOL-17Β AND SOME BLOOD BIOCHEMICAL ATTRIBUTES DURING DIFFERENT GESTATION PERIODS IN IRAQI FEMALE DROMEDARY CAMELS (CAMELUS DROMEDARIUS) - Abdulkareem, Talal Anwer; Al-Rawi, Hani Muneeb; Abdul-Rahaman, Yassen Taha (Emirates Journal of Food and Agriculture, 2015)
This study was conducted to demonstrate the plasma profile of progesterone, estradiol-17β and some blood biochemical attributes (glucose, cholesterol concentrations and alkaline phosphates activity) of Iraqi female dromedary camels (Camelus dromedarius) during different gestation periods.. This experiment included 5 multiparous, non-lactating Iraqi one-humped female camels (Camelus dromedarius) of 7- 8 years old. Blood was collected from female camels at days 20, 30, 40, 50, 60, 90, 120, 150 and 180 post-mating (PM). The plasma progesterone concentrations did not significantly differ among days 20-120 PM. Greater (P≤ 0.05) progesterone concentrations were observed at days 150 and 180 PM as compared with days.20, 30 and 40 PM. No remarkable alterations in plasma estradiol-17β concentrations were seen among different gestation periods. Non- significant variations were detected in plasma glucose concentrations during the entire gestation periods studied (day 20-60 PM). Higher (p<0.05) cholesterol concentrations were observed at days 20 (9.86 ± 0.59 mg/ dl) and 30 (8.84 ± 0.32 mg/ dl) in comparison with their counterpart values at days 50 (7.06 ± 0.1 mg/ dl) and 60 (6.29 ± 0.26 mg/ dl) PM. The overall mean of plasma alkaline phosphatase activity did not alter during the whole study period. In conclusion, the pronounced changes during gestation period in dromedary camels and be detected through sex hormones and plasma cholesterol concentrations.